Stress T1 Mapping in Hypertrophic Cardiomyopathy: Investigating Adenosine Administration Time for Adequate Vasodilation - Ki Seok Choo (Journal of the Korean Society of Radiology)
See the article, “Stress T1 Mapping in Hypertrophic Cardiomyopathy: Investigating Adenosine Administration Time for Adequate Vasodilation”, in volume 86 on page 381-388 (https://doi.org/10.3348/jksr.2025.0017).